2013
DOI: 10.1021/jp311982d
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Transport in Amorphous Al2O3 and AlF3 for Discovery of Battery Coatings

Abstract: Lithium batteries have become a dominant power source for portable electronic devices and also for electric vehicles because of their superior energy density. Electrode coating materials, including amorphous metal oxides and fluorides, are beneficial to improve battery performance such as durability and safety. We use methods that combine first principles density functional theory calculations and statistical mechanics to investigate Li transport in amorphous Al 2 O 3 and AlF 3 . Because of unfavorable Li bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 36 publications
6
99
0
Order By: Relevance
“…Instead, the diffusion was directly modeled by applying periodic boundary conditions to the simulation cell where the Cs interstitial sites were identified by the DFT calculations. A similar approach in a finite cell with periodic boundary conditions successfully modeled the Li diffusion in amorphous (a-) materials, e.g., a-Si 51 , a-Al2O3 52 , and a-AlF3 52 , where they generally showed good agreements with experimental diffusion rates when the comparison was possible.…”
Section: Kinetic Monte Carlo Modelmentioning
confidence: 93%
“…Instead, the diffusion was directly modeled by applying periodic boundary conditions to the simulation cell where the Cs interstitial sites were identified by the DFT calculations. A similar approach in a finite cell with periodic boundary conditions successfully modeled the Li diffusion in amorphous (a-) materials, e.g., a-Si 51 , a-Al2O3 52 , and a-AlF3 52 , where they generally showed good agreements with experimental diffusion rates when the comparison was possible.…”
Section: Kinetic Monte Carlo Modelmentioning
confidence: 93%
“…The Li diffusivity in the layered-structured Li x MO 2 material is relatively low, in the range of 10 -8 to 10 -13 cm 2 /s. [23][24][25][26] In the solid electrolyte "blue" materials Li 10 GeP 2 S 12 and Li 7 P 3 S 11 , the diffusivity is faster, in the range of about 10 -6 -10 -7 cm 2 /s, which is ≥2 orders of magnitude faster than that in the "red" Li x MO 2 . This heterostructured cathode material could be intercalated primarily through the fast "blue" material, requiring Li migration through only a few nanometers in the "red" high-voltage material.…”
Section: Utilization Of Multiple-redox Transition Metal Atoms With a mentioning
confidence: 98%
“…Some possible specific pairs of the "red" and "blue" materials could be Li x NiO 2 as the high-voltage "red" material and a solid electrolyte material (e.g. Li 10 GeP 2 S 12 or Li 7 P 3 S 11 ) as the low-voltage "blue" material. The Li diffusivity in the layered-structured Li x MO 2 material is relatively low, in the range of 10 -8 to 10 -13 cm 2 /s.…”
Section: Utilization Of Multiple-redox Transition Metal Atoms With a mentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic-layer deposition of Al 2 O 3 has been used to provide ultrathin (a few nm) and uniform coatings. Using DFT methods, Hao et al 155 showed that Li diffusion in Al 2 O 3 through the interstitial mechanism is slow. Jung et al 156 studied Al 2 O 3 lithiation to form amorphous Li-Al 2 O 3 coating layers using AIMD and found that the Li diffusion is significantly enhanced at the lithiated state.…”
Section: Silicon and Other Anodesmentioning
confidence: 99%